Quality control and characterization of the testicles and ovaries of irradiated Anastrepha obliqua from Brazil (Scientia Agricola, 2020)
With the aim of making the application of the Sterile Insect Technique (SIT) feasible in the management of the West Indian fruit fly in Brazil, Anastrepha obliqua (Macquart) (Diptera: Tephritidae), a number of quality parameters required by the SIT were investigated in this study. The aim was to verify the influence of a range of doses of gamma radiation (40, 50, 60, 70 and 80 Gy) on the fertility of females and to evaluate several quality control parameters, such as fly emergence, sex ratio, flight ability and survival under stress, as well as the characterization of the morphology (measurement of length and width) of the ovaries and testicles of A. obliqua. Pupae with 24 h before adult emergence were irradiated at CENA/Universidade de São Paulo. The radiosterilization test showed no difference between treatments for the parameters of fly emergence, sex ratio and survival under stress. The radiation at doses above 40 Gy resulted in ovarian atrophy in females and the absence of egg production. In males, the radiation also affected testicular development. Considering the quality parameters assessed, the sterilization results obtained agreed with previous data in the literature for other A. obliqua strains, and the dose of 60 Gy could be considered as the best compromise between insect quality and full sterility for the Brazilian strain of A. obliqua evaluated.